2020
DOI: 10.1152/ajpcell.00485.2019
|View full text |Cite
|
Sign up to set email alerts
|

Synemin-related skeletal and cardiac myopathies: an overview of pathogenic variants

Abstract: This review analyzes data concerning patients with cardiomyopathies or skeletal myopathies associated with a variation in the intermediate filament (IF) synemin gene ( SYNM), also referred to as desmuslin ( DMN). Molecular studies demonstrate that synemin copolymerizes with desmin and vimentin IF and interacts with vinculin, α-actinin, α-dystrobrevin, dystrophin, talin, and zyxin. It has been found that synemin is an A-kinase-anchoring protein (AKAP) that anchors protein kinase A (PKA) and modulates the PKA-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Mutations in DES (OMIM *125660) or LMNA gene (OMIM *150330) cause striated muscle disorders, including desmin-related myopathy and cardiomyopathy (desminopathy) [40], Emery-Dreifuss Muscular Dystrophy (EDMD2, OMIM # 181350 and EDMD3, OMIM # 616516, due to LMNA mutations), LMNA-related congenital muscular dystrophy (L-CMD, OMIM # 613205), limb-girdle muscular dystrophy type 1B (LGMD1B) and LMNA-linked dilated cardiomyopathy with conduction system defects (CMD1A, OMIM # 115200) [41][42][43][44][45][46]. Recently, synemin mutations (SYNM gene, OMIM *606087) have been linked to dilated cardiomyopathy (DCM), while skeletal muscle disease has never been described [11,47]. In particular, four autosomal dominant mutations in SYNM have been associated to DCM [48].…”
Section: Striated Muscle Disorders Caused By Mutations In Intermediate Filament Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in DES (OMIM *125660) or LMNA gene (OMIM *150330) cause striated muscle disorders, including desmin-related myopathy and cardiomyopathy (desminopathy) [40], Emery-Dreifuss Muscular Dystrophy (EDMD2, OMIM # 181350 and EDMD3, OMIM # 616516, due to LMNA mutations), LMNA-related congenital muscular dystrophy (L-CMD, OMIM # 613205), limb-girdle muscular dystrophy type 1B (LGMD1B) and LMNA-linked dilated cardiomyopathy with conduction system defects (CMD1A, OMIM # 115200) [41][42][43][44][45][46]. Recently, synemin mutations (SYNM gene, OMIM *606087) have been linked to dilated cardiomyopathy (DCM), while skeletal muscle disease has never been described [11,47]. In particular, four autosomal dominant mutations in SYNM have been associated to DCM [48].…”
Section: Striated Muscle Disorders Caused By Mutations In Intermediate Filament Proteinsmentioning
confidence: 99%
“…Mutations in synemin have been associated to dilated cardiomyopathy (Figure 3). In particular, two missense mutations in the protein C-terminus, a frame-shift and a nonsense mutation appear to interfere with protein binding to costameric proteins or protein assembly, respectively [47]. Moreover, SYNM has been proposed as a candidate gene for a rare heart-hand syndrome (HHS) referred to as ulnar-mammary-like syndrome [49].…”
Section: Synemin-related Cardiac Disordersmentioning
confidence: 99%
“…This idea is supported by the fact that IFs can withstand deformations of up to 300% of their initial length without rupturing [89]. Several IFs are expressed and developmentally regulated in human skeletal muscle cells [90][91][92][93]. Non muscle-specific proteins vimentin and nestin are expressed in MCPs and myoblasts and are downregulated during later differentiation [94].…”
Section: Cytoplasmic Ifsmentioning
confidence: 99%
“…Desmin, the muscle-specific IF protein, is expressed at low levels in MCPs and its expression continuously increases to become the prominent IF in mature myofibers [94,95]. It can form copolymers with synemin, another non-muscle specific IF, around the α-actininrich Z-lines [92]. In undifferentiated myoblasts, vimentin and desmin are stably linked to the outer nuclear membrane [96] via plectin [97], thus contributing to the perinuclear cage-like structure.…”
Section: Cytoplasmic Ifsmentioning
confidence: 99%
“…The functional outcome of the point mutations is less obvious since these mutations are not within any known binding sites. However, in silico analysis has revealed that missense mutation W538R is predicted to disrupt local residue interaction (Paulin et al, 2020). Specifically, replacement of tryptophan (a neutral apolar hydrophobic residue) with arginine (a positive hydrophilic residue) is predicted to result in loss of interaction between residue 538 and residue leucine 541.…”
Section: Synemin Mutations In Diseasementioning
confidence: 99%